2014
DOI: 10.1016/j.jctb.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton cycles in dense vertex-transitive graphs

Abstract: Abstract. A famous conjecture of Lovász states that every connected vertex-transitive graph contains a Hamilton path. In this article we confirm the conjecture in the case that the graph is dense and sufficiently large. In fact, we show that such graphs contain a Hamilton cycle and moreover we provide a polynomial time algorithm for finding such a cycle.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Given a graph G and a partition of V (G) into clusters of equal size, let R d (G) be the graph whose vertices correspond to clusters and where an edge indicates that the bipartite graph induced by the corresponding clusters is ε-regular with density at least d. If there is a connected component of R d (G) which contains a matching covering at least (α + d)v(R d (G)) of the vertices of R d (G), then there are paths and even cycles in G of each length up to αv(G). In fact, a stronger result is true, as observed by Hladký, Krá ' l and Piguet (see [6], where this idea was also used): we need only a fractional matching with weight (α + d)v(R d (G)). In this subsection we state the corresponding result for tight paths and cycles in k-graphs.…”
Section: Cycle Embedding Lemmamentioning
confidence: 94%
“…Given a graph G and a partition of V (G) into clusters of equal size, let R d (G) be the graph whose vertices correspond to clusters and where an edge indicates that the bipartite graph induced by the corresponding clusters is ε-regular with density at least d. If there is a connected component of R d (G) which contains a matching covering at least (α + d)v(R d (G)) of the vertices of R d (G), then there are paths and even cycles in G of each length up to αv(G). In fact, a stronger result is true, as observed by Hladký, Krá ' l and Piguet (see [6], where this idea was also used): we need only a fractional matching with weight (α + d)v(R d (G)). In this subsection we state the corresponding result for tight paths and cycles in k-graphs.…”
Section: Cycle Embedding Lemmamentioning
confidence: 94%
“…In the special case of dense vertex-transitive graphs (which are always regular), Christofides, Hladký and Máthé [7] introduced a partition into 'iron connected components'. (Iron connectivity is closely related to robust expansion.)…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, the method introduced by Luczak allows us to lift large connected matchings in a reduced graph R i to large cycles in the corresponding G i . In fact, Christofides et al [12] observed that the same is also true for fractional matchings and similarly, 2-matchings. Formally, the following statement holds:…”
Section: Regularitymentioning
confidence: 75%